2018
DOI: 10.1039/c8ob00238j
|View full text |Cite
|
Sign up to set email alerts
|

A visible-light photocatalytic thiolation of aryl, heteroaryl and vinyl iodides

Abstract: The general catalytic synthesis of aryl and vinyl thioethers from readily available halides remains a challenge. Herein we report a unified method for the thiolation of aryl and vinyl iodides with dialkyl disulfides using visible light photoredox catalysis. A range of thioether products bearing diverse functional groups can be accessed in high yield and with excellent chemoselectivity. We demonstrate the versatility of this method through the expedient synthesis of a family of thioether-rich natural products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Aryl and vinyl sulfides 178 were obtained by Polyzos (Scheme 61) via the thiolation of aryl and vinyl iodides 176 with dialkyl disulfides 177, as the source of thiyl radicals, using visible-light photoredox catalysis. 86 This procedure afforded a range of sulfides 178 bearing diverse functional groups in moderate to good yields and with excellent chemoselectivity. The versatility of the method was demon-strated by its application to a family of natural products bearing multiple sulfide functionalities.…”
Section: Scheme 60 Oxidative Dithioacetalization or Thioetherification Of Benzyl Alcoholsmentioning
confidence: 99%
“…Aryl and vinyl sulfides 178 were obtained by Polyzos (Scheme 61) via the thiolation of aryl and vinyl iodides 176 with dialkyl disulfides 177, as the source of thiyl radicals, using visible-light photoredox catalysis. 86 This procedure afforded a range of sulfides 178 bearing diverse functional groups in moderate to good yields and with excellent chemoselectivity. The versatility of the method was demon-strated by its application to a family of natural products bearing multiple sulfide functionalities.…”
Section: Scheme 60 Oxidative Dithioacetalization or Thioetherification Of Benzyl Alcoholsmentioning
confidence: 99%
“…We extended the screen to other amine bases and found that DABCO significantly improve the product yield to 55% (Table , entries 5–7). Effectively, Polyzos and co‐workers reported a visible light photocatalytic method for thioether formation from aryl iodides and disulfide, and DABCO served as single electron donor in the photocatalytic cycle . Subsequently, DABCO was chosen as the base and various catalysts including commonly used iron catalysts (Table , entries 10–12), nickel catalysts (Table , entries 13–15) and palladium catalysts (Table , entries 16–18) were screened.…”
Section: Figurementioning
confidence: 99%
“…unified method for the thiolation of aryl or vinyl iodides with dimethyl disulfide by using the visible-light photocatalyst fac-Ir(ppy) 3 has been reported by Polyzos's group. 30 Nevertheless, each of the procedures discussed above entails various disadvantages, such as the need to use expensive metals, stoichiometric amounts of transition-metal sources, appropriate ligands, prefunctionalized substrates, organic peroxides, environmentally damaging organic solvents, or harsh reaction conditions. Undoubtedly, an efficient and environmentally benign synthetic procedure would still be much appreciated.…”
Section: Letter Syn Lettmentioning
confidence: 99%